Comprehensive Measures for Reducing Perinatal Blood Loss - S. Yu. Timokhova; V. V. Golubtsov (Общая реаниматология)
Objective: to develop a procedure to reduce perinatal blood loss, by permitting the lower use of allogeneic blood. Subjects and methods. The investigation enrolled 96 female patients with moderate and severe preeclampsia, whose status was complicated by massive blood loss. The women were divided into 2 groups: a study group (n=55) that was treated by a package of proposed measures and a control group (n=41) that was retrospectively assessed. During the study, the investigators made a dynamic assessment of peripheral blood parameters and hemostatic system markers, monitored blood and central venous pressures, hourly and daily diuresis, acid base and water electrolyte balance parameters, and collected medical history data. Results. The investigation established that a package of proposed measures to reduce massive obstetric blood loss significantly accelerated the restoration of general clinical and biochemical parameters in the early postoperative period. Conclusion. The proposed procedure is easy-to-use and it is of obvious practical use because it can reduce the use of donor blood components by twice and the length of hospital stay by 6. 5 bed-days.